Development of a Positive Selection High Throughput Genetic Screen in Dictyostelium discoideum - Williams, Felicia N.; Wu, Yumei; Scaglione, K. Matthew (Frontiers in Cell and Developmental Biology, 2021)
The cellular slime mold Dictyostelium discoideum is a powerful model organism that can be utilized to investigate human health and disease. One particular strength of Dictyostelium is that it can be utilized for high throughput genetic screens. For many phenotypes, one limitation of utilizing Dictyostelium is that screening can be an arduous and time-consuming process, limiting the genomic depth one can cover. Previously, we utilized a restriction enzyme-mediated integration screen to identify suppressors of polyglutamine aggregation in Dictyostelium. However, due to the time required to perform the screen, we only obtained ~4% genome coverage. Here we have developed an efficient screening pipeline that couples chemical mutagenesis with the 5-fluoroorotic acid counterselection system to enrich for mutations in genes of interest. Here we describe this new screening methodology and highlight how it can be utilized for other biological systems.